Life‐course social influences on tooth loss and oral attitudes among older people: evidence from a prospective cohort study. (8th December 2014) - Åstrøm, Anne N.; Ekback, Gunnar; Lie, Stein A.; Ordell, Sven
<x xml:space="preserve">Abstract</x> This study examined the relationship of trajectories in social condition with oral attitudes and major tooth loss, using the social mobility and accumulation life‐course models in a cohort. Whether social‐condition inequalities remained stable or changed from 65 yr of age to 70 yr of age was investigated. In 1992, 6, 346 inhabitants born in 1942 and residing in two Swedish counties agreed to participate in a prospective survey. Of the participants in 1992, 3, 585 (47.6% men) completed questionnaires in 1997, 2002, 2007, and 2012. In line with the social‐mobility model, the prevalence of negative oral attitudes and major tooth loss in participants at 65 and 70 yr of age showed a consistent gradient according to social‐condition trajectory, whereby it was lowest among those who were persistently high and highest among those who were persistently low, with the upwardly and downwardly mobile categories being intermediate. A linear graded association between the number of periods with disadvantaged social condition and oral health supported the accumulation model. Both the social mobility and accumulation life‐course models were supported. Social‐condition differentials in negative oral attitudes and tooth loss seem to remain stable or to narrow weakly after the usual age of retirement.